2022
DOI: 10.2147/ppa.s347394
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ Satisfaction with Ophthalmology Clinic Services in a Public Teaching Hospital

Abstract: To evaluate patients' satisfaction with ophthalmology health services in a teaching clinic of a tertiary public hospital. Patients and Methods: This was a cross-sectional study in ophthalmology clinic of Dr. Sardjito teaching hospital, Yogyakarta, Indonesia conducted in 2019. Patients were surveyed using the Patient Satisfaction Questionnaire-18 (PSQ-18). PSQ-18 subscale score was analyzed based on patients' characteristics. The main outcome was the odds of reaching top satisfaction score (TSS) of 4-5 from a L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…In addition, since glaucoma necessitates lifelong follow-up and treatment, longer follow-up periods not only enhance patients' understanding of the disease but also foster greater trust in case managers over extended interactions. Previous studies have identified technical quality or interpersonal manner of the doctor as the highest-rated dimensions of patient satisfaction [14,[30][31][32] . In contrast, our study found that communication dimension received the highest scores.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, since glaucoma necessitates lifelong follow-up and treatment, longer follow-up periods not only enhance patients' understanding of the disease but also foster greater trust in case managers over extended interactions. Previous studies have identified technical quality or interpersonal manner of the doctor as the highest-rated dimensions of patient satisfaction [14,[30][31][32] . In contrast, our study found that communication dimension received the highest scores.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of careful listening from medical staff is a common problem in large hospitals when the number of patients is too large, and pharmacists do not have enough time to listen to each customer. However, the availability and active listening from medical staff were among the least satisfactory and most essential items of medical care [ 49 , 50 , 51 ]. Therefore, our study suggests that the hospital could arrange reasonable human resources during peak hours and open more client care counters or mobile lines in order to have more time to listen to patient requests.…”
Section: Discussionmentioning
confidence: 99%
“…The PSQ-18 is a reliable and valid tool that has been used in various healthcare settings to evaluate PS. 6 7 Due to its ease of administration and provision of valuable information for improving care quality, the PSQ-18 is suitable for assessing PS with paediatric health services at tertiary hospitals.…”
Section: Introductionmentioning
confidence: 99%